PPENGEMBANGAN LEMBAR KEGIATAN SISWA (LKS) DILENGKAPI GAMBAR PADA MATERI SISTEM PEREDARAN DARAH UNTUK SISWA SMA/MA - Sari, Puspita Irlina; Ardi, Ardi; Risdawati, Renny (STKIP PGRI Sumbar, 2013)
ABSTRACTBiology consists of manyÂ concepts so students are required to understand the concept-the concept of biology. To facilitate and direct the students will need for media/ learning device that can help students in understanding the concepts-concepts of biology, one of the worksheets, after the observation, students learn biology MAN 1 Padang using student activity sheet (LKS) were purchased in the market. In the opinion of same student look unattractive LKS, the image is not clear and colorless. Authors had expected this led to student motivation ang learning outcomes to be low, it is therefore necessary to develop worksheets that students are expected to be able to motivate and anable students to master or understand the biology of learning materials. Type of research is the development ( development research) with procedural model. Developed using 4-D models that been modified , define ( definition ), design ( design), develop ( development). Based on the results of the validity and practicalities LKS vaid and practical categories.Â